Effect Of Environmental Performance, Environmental Costs, And Corporate Social Responsibility On Financial Performance Of Mining Companies Listed On The Indonesia Stock Exchange In 2020-2022 - Naela Cahaya Putri; Muhammad Abdul Aris (SEAN Institute, 2024)
Financial performance is a metric to assess the success of a company in its operations and profit, in assessing whether the financial performance of a company is good or not, the necessary step is to analyze its financial statements. This study aims to determine the effect of environmental performance, environmental costs, and corporate social responsibility on financial performance. This research is included in the category of quantitative research based on the use of this type of data. The Data used is secondary data. The population used in determining the sample of this study is mining companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. Sampling method using purposive sampling, and obtained a final sample of 34 data. This study will use quantitative research methods by applying multiple linear regression analysis to analyze data. The results of this study showed that environmental performance does not affect financial performance, while environmental costs and corporate social responsibility affect financial performance.